Organisational learning from the public health response to the COVID-19 pandemic: findings from a qualitative interview study - Southworth, Felicity; Chalmers, Daljinder; Reedy, Gabriel; Amlôt, Richard; Skryabina, Elena (Frontiers in Public Health, 2024)
System learning from major incidents is essential for enhancing preparedness for responding to future adverse events. Sharing learning not only stimulates further improvements, preventing the repetition of mistakes, but may also promote collaboration and the adoption of evidenced-based best practises. As part of a qualitative interview study designed to explore lessons learned, this paper describes the experiences and perspectives of 30 staff from the public health agency responsible for the national COVID-19 response in the United Kingdom. The focus of the interviews was on enabling factors and practises that worked well, as well as those that were more challenging, and which, if addressed, could improve responses to future infectious disease incidents. The interviews elicited valuable insights across various thematic areas that could inform emergency preparedness activities for future infectious disease outbreaks. The outcomes of this study, while integral for the UK agency responsible for public health, extend beyond organisational boundaries and contribute to a broader spectrum of activities aimed at facilitating global learning from the COVID-19 response.